Penilaian Kinerja Keuangan Berdasarkan Rasio Profitabilitas, Likuiditas, Solvabilitas dan Aktivitas: Studi Kasus Perusahaan Manufaktur Subsektor Makanan dan Minuman 2019-2023 - Monica Mega; Maya Widyana Dewi; Suprihati (Nur Science Institute, 2026)
This research aims to determine the influence of financial ratios on financial performance in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2019 - 2023 period. Net Profit Margin (NPM), Current Ratio (CR), Debt to Asset Ratio (DAR), Total Assets Turnover (TATO) as the independent variable and Return On Assets (ROA) as the dependent variable. The population of food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (BEI) is 25 companies, which were then selected using a purposive sampling method and resulted in a sample of 15 companies. The data analysis techniques used in this research are Multiple Linear Regression Analysis, F Test, t Test and Coefficient of Determination Test. The results in this study show that Net Profit Margin (NPM), Debt to Asset Ratio (DAR), Total Assets Turnover (TATO) have an effect on financial performance while the Current Ratio (CR) has no effect on financial performance. Meanwhile, all independent variables simultaneously influence financial performance.